Health and Social Issues Related to Confidential Births - Petržílková, Helena; Čermák, Zdeněk; Malinová, Lenka (University of Pardubice, 2017)
Introduction: The article describes the current Czech legal regulation of the area of confidential births with respect to actions that must be taken by healthcare providers, covering all phases including adoption, foster care or institutional care of the child, with an emphasis placed on the social and legal protection of children. Furthermore, the paper describes the controversy concerning real maternal anonymity. Objective: The aim of the article is to describe the current Czech health and social legislative theory and practice in the field of confidential births and subsequent care. Method: With regards to the theoretical nature of the article, the methods of analysis and compilation of expert texts were used. Results: The current Czech legal regulation allows women to give a so-called confidential birth. Healthcare institutions have specific procedures in place, respecting the relevant legal regulations concerning the subject matter. Nevertheless, the mother continuously faces a disclosure of her identity in the course of guardianship-related proceedings regarding placing the child for adoption, into foster care or institutional care. Under the existing legal regulation, comprehensive legal approaches to confidential births and aftercare are set to protect the anonymity of the mother, but not entirely. Conclusion: The current system of law enables women to give confidential births in official healthcare facilities. However, real anonymity is not guaranteed due to the disclosure of the mother’s identity while reporting the provided health care to the health insurance company and in the course of legal guardianship proceedings concerning the child.
Keywords: confidential birth; mother’s identity; social and legal protection of children